Spatial Suitability of Solar Energy Production in the Garmian Administration implementing Multi-Criteria Decision Making (MCDM) Methods (Raparin Journal of Humanities (RJH), 2025)
This research was conducted in the field of applied climatology & relied on several technics, software programs, and advanced geographical methods. The research area encompasses Garmian District, which is located in the southeastern part of the Kurdistan Region. It borders Sulaymaniyah Province to the north, Halabja Province to the northeast, Kirkuk Province to the northwest, Saladin Province to the west, and Diyala Province to the west and southwest. In addition to that, on its eastern side, it shares a 122.5 km border with Kermanshah Province. The total area of the Garmian District is approximately (6,017.95Km2). The research area encompasses Kifri & Khanaqin Districts, as well as Maydan & Qoratoo sub districts. The main objective of this study is to determine the most suitable site for the installation of solar energy plants in the Garmian District, with the goal of addressing the electricity shortage in the research area by providing an optimal solution. In conclusion, the physical characteristics of the study area are highly suitable for the installation of photovoltaic power plants. Specifically, around half of the research area is considered very well-suited for this purpose.